The Influence of Critical Land to Reduce Flood in Arau Watersheds at Padang City- Indonesia - Utama, Lusi; Amrizal,; Berd, Isril; Zuherna, (International Journal of Psychosocial Rehabilitation, 2020)
Flood is a natural phenomenon that often occurs. The parameters causing floods are due to high rainfall, changes in land use, illegal logging, damaged drainage and lack of government attention in making policies. The city of Padang from 2008 - 2018 often flooded. Indonesia is a country that has 2 seasons, the dry season and the rainy season. So that the benefits of water can be used for needs, so during the rainy season, this water can be used as a reserve of water in the dry season. From research conducted on the Arau watershed, that there are 8 SUB Arau watersheds experiencing flooding. To reduce the flooding that occurs, critical land is used in each SUB watershed. The calculation of rainfall using rainfall data from 2005 - 2017 and Thiessen theory on rainfall data from 5 stations to get rainfall plans. Water debit calculations use rational formulas. Conservation of degraded land into developed land in the form of green land and forests obtained for the largest area of green land required in the Baringin SUB Watershed and the largest forest area needed in the Lubuk Kilangan SUB Watershed.